Prospect of Sugar Cane by Products as a Feedstuffs for Beef Cattle Fattening in Dry Regions - M, Zulbardi; Sugiarti, Tatit; Hidayati, N; Karto, Abdurrays Ambar (Indonesian Animal Sciences Society, 1999)
Several by product of sugar cane can be utilized as roughage. So that cooperation between sugar processing industries and beefcattle industries is enable to enhance. In Indonesia, about 4.62 million ton sugar cane tops, 1 .98 million ton klentekan and 1.32 million ton sugar sogolan can be obtained each year. By product of sugar processing can yield bagasse, blotong and molasses . All of these by products are potential as substitute for common forage in ruminants particularly during a relatively long dry season as long as protein sources are provided. Key words : Feedstuths, by product